IL-17RA receptor signaling contributes to lung inflammation and parasite burden during Toxocara canis infection in mice - Leal-Silva, Thaís; Lopes, Camila de Almeida; Vieira-Santos, Flaviane; Oliveira, Fabrício Marcus Silva; Kraemer, Lucas; Padrão, Luiza de Lima Silva; Amorim, Chiara Cássia Oliveira; Souza, Jorge Lucas Nascimento; Russo, Remo Castro; Fujiwara, Ricardo Toshio; Magalhães, Luisa Mourão Dias; Bueno, Lilian Lacerda (Frontiers in Immunology, 2022)
IL-17 is a cytokine produced by innate and acquired immunity cells that have an action against fungi and bacteria. However, its action in helminth infections is unclear, including in Toxocara canis infection. Toxocariasis is a neglected zoonosis representing a significant public health problem with an estimated seroprevalence of 19% worldwide. In the present study, we describe the immunopathological action of IL-17RA in acute T. canis infection. C57BL/6j (WT) and IL-17RA receptor knockout (IL-17RA-/-) mice were infected with 1000 T. canis eggs. Mice were evaluated 3 days post-infection for parasite load and white blood cell count. Lung tissue was harvested for histopathology and cytokine expression. In addition, we performed multiparametric flow cytometry in the BAL and peripheral blood, evaluating phenotypic and functional changes in myeloid and lymphoid populations. We showed that IL-17RA is essential to control larvae load in the lung; however, IL-17RA contributed to pulmonary inflammation, inducing inflammatory nodular aggregates formation and presented higher pulmonary IL-6 levels. The absence of IL-17RA was associated with a higher frequency of neutrophils as a source of IL-4 in BAL, while in the presence of IL-17RA, mice display a higher frequency of alveolar macrophages expressing the same cytokine. Taken together, this study indicates that neutrophils may be an important source of IL-4 in the lungs during T. canis infection. Furthermore, IL-17/IL-17RA axis is important to control parasite load, however, its presence triggers lung inflammation that can lead to tissue damage.